Adherencia al tratamiento en pacientes con enfermedad pélvica inflamatoria mediante seguimiento farmacoterapéutico, atendidas en el Hospital III Iquitos - EsSalud 2022 - Mendoza Mendoza, Milagros del Rosario (2024)
The purpose of this research was to determine the benefits of adherence to treatment in patients with pelvic inflammatory disease, through pharmacotherapeutic monitoring attended in the Gynecology-obstetrics office of Hospital III Iquitos - EsSalud 2022, the study methodology was quantitative. prospective, analytical, observational and cross-sectional design, the population consisted of 40 patients who presented pelvic inflammation, the methodology was through pharmacotherapeutic monitoring and the Morisky Green test to determine adherence to treatment, the results obtained were: The PRMs detected were PRM5 with 40.0%, PRM4 with 32.5% and PRM3 with 27.5%. The therapeutic adherence was 67.5% after pharmacotherapeutic follow-up, it is concluded that there was adherence to the treatment in patients with pelvic inflammatory disease, which allowed morbidity to be reduced, improving the effectiveness of medications in the Gynecology-Obstetrics office of Hospital III Iquitos - EsSalud during the period January to June 2022.